The Effect Of Vark (Visual Auditory Read/Write Kinesthetic) Strategy Toward Students’ Reading Comprehension (A Quasi Experimental at Second Grade Students’ of SMAN 3 Kota Bengkulu) - Herlita, Ana (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to investigate the effect of the VARK (Visual, Auditory, Read/Write, Kinesthetic) learning strategy on students’ reading comprehension in the second grade at SMAN 3 Kota Bengkulu. Reading is a vital skill for senior high school students, as it enhances their ability to acquire new knowledge, support ideas, and complete academic assignments. This study employs a quasi-experimental design with 68 students as participants. Class XI J was selected as the experimental group, receiving the VARK strategy, while class XI G was the control group, using convensional teaching methods. The results show a significant effect of the VARK strategy on students’ reading comprehension, with a p-value of 0.000. These findings suggest that the VARK strategy can enhance reading comprehension by catering to different learning preferences, creating a more inclusive and effective learning environment. Keywords : (Reading Comprehension, VARK (Visual Auditory Read/write Kinesthetic) Strategy)